Effect of ceramic‐based coatings deposited on low‐alloyed steel T/P22 10H2M exposed at high temperature. Issue 3 (2nd February 2021) - Rząd, Ewa; Polczyk, Tomasz; Boroń, Łukasz; Figiel, Paweł; Solecka, Monika; Dudziak, Tomasz; Oziębło, Artur; Chmielewska, Danuta; Synowiec, Barbara; Pichniarczyk, Paweł
Abstract: The study was carried out in order to evaluate oxidation resistance of the ceramic coatings based on SiO2 ‐B2 O3 ‐TiO2 ‐Na2 O composition deposited on the low‐alloyed steel T/P22 (10H2M) surface exposed for 1000 h at 540°C in oxidation atmosphere. Kinetic data were recorded periodically every 250 h; macro‐ and microanalyses as well as chemical composition were carried out using macrolenses, SEM, EDS, EDS X‐ray mappings. The results indicated a high degree of protection by ceramic coatings; much lower mass gain was observed for the coated materials than for the uncoated T/P22 (10H2M) steel. No detachment, delamination, chipping of a coating were found from the steel surface; some of the coatings showed perpendicular tiny cracks to the bulk metal surface.